Stress Coping Strategies In Farmers As An Effort To Overcome Psychosocial Problems - Kurniyawan, Enggal Hadi; Nurfatekha, Esa Darma; Aisyah, Rifanti Dwi; Putri, Chicha Amilia; Nur, Kholid Rosyidi Muhammad; Kurniawan, Dicky Endrian; Afandi, Alfid Tri (International Journal of Midwifery and Health Sciences, 2024)
Introduction: Agriculture plays a crucial role in Indonesia, with farmers as the backbone of this sector. However, farmers often experience high levels of stress due to workloads and other psychosocial issues. Objective: This study aims to review the literature on coping strategies used by farmers to address their psychosocial problems. Method: A literature review was conducted by searching for relevant articles in databases such as Science Direct, PubMed, and Google Scholar. Keywords related to “stress”, “farmers”, and “coping” were used. Selected articles were published in the last five years (2019-2024). Results: The literature review revealed that farmers employ various coping strategies to manage stress, including good work practices, stress management, mental health counseling, relaxation therapy, and coping strategies focused on problems or emotions. Social support, self-confidence, and self-efficacy also play crucial roles in reducing stress among farmers. Conclusion: Farmers in Indonesia face significant psychosocial challenges, but they demonstrate the ability to address these issues through various coping strategies. Social support and self-confidence are crucial in improving the mental well-being of farmers. The implications of this study emphasize the importance of developing more effective intervention programs to enhance the mental well-being of farmers in Indonesia.